Adalimumab in the treatment of moderate-severe hidradenitis suppurativa: a cost-effectiveness analysis - Borges, Sofia (2018)
Introduction: To assess the cost-effectiveness of adalimumab versus supportive care  in the treatment of adults with active moderate to severe hidradenitis suppurativa who have had an inadequate response to or are intolerant of conventional systemic therapy in Portugal.Methods: A Markov model with 5 health states (high response, response, partial response, non-response, or death) and 4-week cycles was developed to estimate long-term effectiveness and cost of treating patients with adalimumab versus supportive care. Data from head-to-head clinical trials (PIONEER I and II) were used to estimate transition probabilities and utilities. Resource use was characterized by Portuguese experts’ panel. Unitary costs were extracted from national official sources and expressed in 2015 euros. Incremental cost per quality adjusted life years gained was estimated for a lifetime horizon in the societal perspective, assuming a 3.5% annual discount rate for costs and consequences. Deterministic and probabilistic sensitivity analyses were performed.Results: From the societal perspective, for a lifetime horizon, the model predicted a cost of €241,957 for adalimumab and €223,903 for supportive care, resulting in 12.32 and 11.55 quality adjusted life years (QALY), respectively. Thus, the incremental cost-effectiveness ratio is estimated to be €23,332/QALY gained (or €35,225/QALY from the Portuguese National Health System perspective). Patients receiving adalimumab incurred more treatment costs (+€39,243), partially offset by less direct medical costs (-€13,130) and indirect costs (-€7,877) than patients receiving supportive care. In deterministic sensitivity analyses, incremental cost-effectiveness ratios ranged between €1,347 (0% discount) and €42,465 (utilities’ assumption). The probability of adalimumab’s cost-effectiveness was 61.2% for a willingness-to-pay threshold of €30,000 and 78% for €50,000.Conclusion: Adalimumab is the first and only drug approved by the European Medicines Agency for Hidradenitis Suppurativa and its cost-effectiveness in Portugal is demonstrated in this economic analysis.